Hydraulics Study of Side Channel Spillway Pasuruhan Dam Magelang Regency Central Java Province with Physical Test Model 1:60 Scale. - Alam, Rizki Robbi Rahman; Taufiq, Mohammad (Jurnal Mahasiswa Jurusan Teknik Pengairan, 2018)
In accordance with the requirements of dam construction in Indonesia, it needsdetailed and directed planning so that at the next stage is the Pasuruhan Dam DesignCertification. At the current stage of the activity will be carried out the physical model buildingtest of the structure of the Pasuruhan Dam plan as well as a study that aims to study the hydraulicperformance and provide results of technical studies on the safety of the dam body in someconditions required. Analysis of water level profiles, debits studied are Q100th, Q1000th, and QPMF.The results of the water level profile analysis, the ability of the overflow when flowing QPMFdischarge does not occur in the body of the dam (ovetopping). Side channel conditions do notoccur back water. The condition of the transition channel is subcritical and there is no cross flow.In the launch channel, the condition is supercritical, there is no cavitation and vibration flow. Thepressure on the spillway, the transition channel, and the launching channel does not applypressure. On the downstream of the river, after the downstream directional channel (EscapeChannel), the deepest scour that occurs is 6 m. To reduce the depth of the scour, rip-rap is addedafter the downstream directional channel and ground sill is added to the downstream of the river.